Hysterectomy rates per resident in final year of training in teaching hospitals: an ecologic study - Luiza Nestori Chiozzotto; Nino José Wilson Moterani Júnior; Laura Bresciani Bento Gonçalves Moterani; Vinicius César Moterani; Francisco José Candido dos Reis (Revista Brasileira de Ginecologia e Obstetrícia)
Abstract Objective: Analyze the hysterectomy rates per resident in graduation year in teaching hospitals in the state of São Paulo (Brazil). Methods: We selected teaching hospitals in the state of São Paulo and gathered information from two public databases to estimate the hysterectomy rates per resident in their final year of training between 2009 and 2019. Results: Between 2009 and 2019, there was a 37.5% increase in the number of residents in their final year of training, a 4.31% increase in the number of hysterectomies, and a drop in the hysterectomy rates per resident of 24.1%. The reduction of the rate of hysterectomy per resident was more pronounced for vaginal route (46.4%) followed by abdominal route (23.3%). The ratio of laparoscopic hysterectomy per resident increased 264% during the period, however, this route was used in only 7% of the surgeries in 2019. Conclusions: The hysterectomy rates per resident in their final year of training showed a notable reduction. This trend, particularly pronounced in vaginal and abdominal routes, signals a shift towards minimally invasive techniques.